ANALISIS MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DALAM MENGEMBANGKAN SIKAP KOLABORATIF SISWA KELAS V DI SEKOLAH DASAR - Tia Nabila, Cindy; Rukmana, Kusman; Nurfadilah, Sidqia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation process of the Teams Games Tournament (TGT) cooperative learning model and to examine the development of collaborative attitudes among fifth grade elementary school students in Science and Social Studies (IPAS) learning at SD Negeri Sindang IV Sumedang. This research employed a qualitative descriptive approach with data collected through structured observation, in-depth interviews, and documentation. The subjects consisted of one fifth-grade teacher and three selected students using purposive sampling. The findings reveal that the teacher implemented all five stages of TGT class presentation, team study, game, tournament, and team recognition systematically and consistently with 100% implementation rate in the Excellent category. After the implementation of TGT, students' collaborative attitudes across five aspects (cooperation, active participation, individual responsibility, peer communication, and sportsmanship) were all categorized as Excellent (100%). However, interview data revealed that individual internalization of collaborative values had not yet been uniform, with some students exhibiting passive behavior, insufficient tournament preparation, and difficulty managing constructive disagreement. This study concludes that the TGT model effectively fosters collaborative attitudes in fifth-grade students, consistent with the cooperative learning (gotong royong) dimension of the Pancasila Student Profile in the Merdeka Curriculum, though sustained implementation is required for deeper and more equitable internalization.